Interpersonal violence: identification of associated features in a clinical sample. (December 2018) - Talevi, Dalila; Imburgia, Lorenzo; Luperini, Chiara; Zancla, Alessandro; Collazzoni, Alberto; Rossi, Rodolofo; Pacitti, Francesca; Rossi, Alessandro
Abstract: Violence is a burdensome problem in daily psychiatric practice, even though the diagnosisof a mental disorder is not sufficient to determine a violent behavior; therefore, other factors are involved. We predicted that the participants could be distributed in two groups (e.g. high versus low violence-maltreatment groups) because this grouping would better describe specific patterns of associations in a clinical sample. We aimed to investigate the relation between interpersonal violence and maltreating experiences in childhood. Affective states and personal functioning were also explored as meaningful outcomes. Consecutive patients (N = 101) admitted to a psychiatric unit were evaluated with the Risky Families Questionnaire, the Psychological Maltreatment Review, the Karolinska Interpersonal Violence Scale (KIVS), the Positive and Negative Affect Schedule and the Personal and Social Performance Scale. Single, with average education and unemployed individuals showed significantly higher KIVS scores. High levels of interpersonal violence (IV) in childhood correlated with a harsh family climate in early life. Moreover, IV correlated with perceived parental maltreatment and did not with parental support. The cluster analysis identified two clusters of patients. The first (n = 41) showed negative dysfunctional experiences; the second (n = 60) showed a more positive perception of parental support.The impairment of social functioning and emotions regulation are both involved in this complex relation. The study supports the hypothesis of a clustering of patients that needs tailored management of violence causes and consequences.